Priming of Solanum Tuberosum in vitro plants with PVY-specific interfering RNAs activates anti-viral resistance - Sutula, M.; Khosnutdinova, T.; Zhakmanova, Yе.; Dolanbayeva , G.; Bogdanova, X.; Yessilbekova , Ye.; Komekova , G.; Kabatayeva , Zh. (Eurasian Journal of Applied Biotechnology, 2022)
Helper component-proteinase (HC-Pro) is a multifunctional suppressor protein synthesized by potato virus Y (PVY), which is able to neutralize the protective mechanisms of RNA interference (RNA-i) in potato plants, thereby causing systemic infection of the host plant and significant damage to the tuber material. This article demonstrates how one of the main functions of HC-Pro, the capture and retention of short interfering RNAs, 21-23 nt in size (siRNA) on the surface of protein subunits, can be used to create virus-resistant potato plants in vitro. The proposed method is based on the selective dissociation of the HC-Pro/siRNA complex from PVY-infected plants and siRNA-priming of healthy plants. Purified preparations of PVY-specific siRNAs were obtained using column gel filtration followed by immunoprecipitation and phenol-chloroform extraction. Injections of siRNA into the leaf plate of virus-free potato microplants, cultivars bred at Amanzholov University, led to a decrease in the accumulation of viral particles in the cytoplasm of plants inoculated with the wild PVY strain and the formation of resistance to PVY for the entire growing season.